Iurij S. Liapunov – a Lost Classicist of the Great War Generation - Budaragina, Olga (Hyperboreus, 2016)
The article presents the tragic fate of Iurij Liapunov (1893–1920), a highly promising classical scholar, the son of composer Sergej Liapunov and a great-grand-son of the famous Russian ethnographer, lexicographer, and man of letters Vladimir Dahl. Having graduated from St. Anne’s German School (Annenschule), Liapunov became a student of the Historical-Philological Faculty of St Petersburg University. Under the supervision of Sergej Zhebelev and Mikhail Rostovtzeff, who were his principal teachers at the Department of Classics, he published two articles in the Journal of the Ministry of Public Education. In 1919, Liapunov was appointed the secretary of the State Hermitage. At the start of 1920, he was called up for military service in the Red Army, and in February of the same year he died of epidemic typhus.